Digitalisasi Pengelolaan PAM Desa: Optimalisasi Pencatatan Meteran Air dengan Barcode Scanning di BUMDES Candi Mulya - Fandy Setyo Utomo; Chyntia Raras Ajeng Widiawati; Anies Indah Hariyanti; Yuli Purwati (JURPIKAT, 2026)
This community service program aims to enhance the efficiency and transparency of clean water service management in Candinegara Village by implementing a barcode scanning-based water meter recording system. Problems faced by the Candi Mulya Village-Owned Enterprise (BUMDES) include manual recording errors, late billing, and a lack of transparency in water usage data. To address these issues, a Progressive Web App (PWA) for customers and a monitoring dashboard for administrators were developed, enabling real-time data monitoring. Implementation methods included outreach, application usage training, and the implementation of a barcode scanning system for meter recording. Evaluation results through a questionnaire distributed to 28 respondents showed a Perceived Usefulness (PU) score of 3.75, Perceived Ease of Use (PEOU) of 3.44, Attitude Toward Using (ATU) of 3.85, and Behavioral Intention to Use (BIU) of 3.63, reflecting positive acceptance of the application. In conclusion, the implementation of a barcode scanning-based digital system has successfully increased the accuracy, efficiency, and transparency of Village Water Supply (PAM) management and received a positive response from the community and BUMDES managers.